Determinantes de la pobreza en el departamento de Boyacá - Amaya Rodríguez, Carlos Andres; Cepeda Rodríguez, Paula Andrea (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
This document assesses the situation of poverty indicators in the department of Boyacá, based on the figures provided for DANE, to identify the determinants and be able to identify a panorama between inequity, poverty and the social condition in Boyacá. Starting from a probabilistic model, it is desired to sift each indicator to arrive at the determinants of this condition and, in turn, determine the probability of poverty in which the inhabitants of the Department find themselves. The foregoing, with the aim of obtaining a tool that allows decision-making in the formulation of public policies that affect the poverty figures in the Department of Boyacá.

El presente documento evalúa la situación de los indicadores de pobreza en el departamento de Boyacá, basados en las cifras aportadas para el DANE para analizar los determinantes y poder identificar un panorama entre la inequidad, la pobreza y la condición social en Boyacá. A partir de un modelo probabilístico se desea tamizar cada indicador para llegar a los determinantes de esta condición y a su vez estimar los factores asociados a la probabilidad de ser pobre en el Departamento. Lo anterior, con el ánimo de obtener una herramienta que permita la toma de decisiones en la formulación de políticas públicas que incidan en las cifras de pobreza en el Departamento de Boyacá.
Keywords: Pobreza; Pobreza monetaria; Pobreza multidimensional; Análisis económico; Poverty; Monetary poverty; Multidimensional poverty; Economic analysis